Study on RIP current of Pengkalan Datu to Kuala Besar, Kelantan / Nik Ali Nik Cob - Nik Cob, Nik Ali (1996)
Rip Current is strong narrow current that flows from the beach towards to the sea. It is one of the main mechanism by which water brought forward to the shore by breaking waves is returned back to the sea to satisfy continuity. Due to its strength and relative difficulty to detect, the presence of rip current is very dangerous especially on beaches used for recreational purposes. The aim of this study is therefore to detect the pattern and location of the rip currents at a selected beach, so as to make it safe for anyone using the beach. Rip currents depend a lot on seabed bathymetry, thus it is also important to relate changes in bathymetry due to sediment transport to shifting of the location of rip currents in the timescale involved.